Administration of DNA Plasmid Coding Protein Aggregating Domain Induces Inflammatory Bone Loss - Agas, Dimitrios; Concetti, Fabio; Capitani, Melania; Lacava, Giovanna; Concetti, Antonio; Marchetti, Luigi; Laus, Fulvio; Marchegiani, Andrea; Azevedo, Vasco; Giovanna Sabbieti, Maria; Maria Venanzi, Franco (Current Gene Therapy, 2016)
Background: Plasmids coding protein aggregation polypeptides from different sources have been proposed as genetic adjuvants for DNA vaccines. We reported that a plasmid (pATRex), encompassing the DNA sequence for the von Willebrand A (vWA/A) domain of the Anthrax Toxin Receptor-1 (ANTXR-1, alias TEM8, Tumor Endothelial Marker 8), acts as strong immune adjuvant by inducing formation of insoluble intracellular aggregates and subsequent cell death. Objective: In the present study we addressed the question of whether there is any substantial immunotoxicity associated with the use of self-aggregating proteins as genetic adjuvants. Methods & Results: Here we report, by mean of histology, X-ray and molecular examinations of bone specimens, the unexpected finding that intramuscular injection of pATRex in mice triggers, per se, severe bone loss (osteoporosis) independently from the sex and genotype of the treated animals. Conclusion: Even though the study suggests that proteinaceous “sticky “ adjuvants are unlikely to find their way into practical vaccination, the information gained is of value as ATRex injections could provide an additional, simplified, mouse model of osteoporosis. Moreover, our results provide experimental support to the hypothesis that proteotoxic aggregates chronically activate the innate immune system in amyloid and aggregosome associated disorders.
Keywords: Osteoporosis